1990
DOI: 10.1111/j.2042-3306.1990.tb04245.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in conformation of Swedish Warmblood horses and conformational characteristics of élite sport horses

Abstract: Summary The variation in conformation of 356 Swedish Warmblood horses is described, using a quantitative method of measuring horses. Thirty‐three of the horses were élite dressage horses, 28 were élite showjumpers, 100 were riding school horses and 195 were unselected four‐year‐olds. Most horses had a long body form. The average height at the withers was 163.4 cm. Sixty per cent of the horses had a bench knee conformation, 50 per cent had a toe‐in conformation of the forelimbs and 80 per cent had outwardly rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
110
4
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(125 citation statements)
references
References 6 publications
10
110
4
1
Order By: Relevance
“…Holmström et al [18] studied the conformational characteristics of elite sport horses and found that elite dressage horses had more sloping shoulders and Holmström and Philipson [19] showed a positive correlation between good gaits and sloping shoulders in warm blood horses. It could then be thought that the inclination of this region with respect to the horizontal plane influences the quality of movement in the fore limb.…”
Section: Discussionmentioning
confidence: 99%
“…Holmström et al [18] studied the conformational characteristics of elite sport horses and found that elite dressage horses had more sloping shoulders and Holmström and Philipson [19] showed a positive correlation between good gaits and sloping shoulders in warm blood horses. It could then be thought that the inclination of this region with respect to the horizontal plane influences the quality of movement in the fore limb.…”
Section: Discussionmentioning
confidence: 99%
“…Breeding aims of most modern Warmblood horse breeds are focused on performance, particularly on performance in riding sports [17]. Several, but not all genetic studies on this topic have shown the relation between particular conformation traits and performance in equestrian sports [11,12,21,22]. Evaluation of and selection for functional conformation is therefore used as a tool for indirect performance selection.…”
Section: Introductionmentioning
confidence: 99%
“…La raza, sexo y edad tienen una influencia significativa sobre la conformación y variables biocinemáticas (Holmström 1990). Es por esto que en el presente estu-Figura 5.…”
Section: Discusionunclassified